Gender differences in body composition, dietary patterns, and physical activity: insights from a cross-sectional study - Lombardo, Mauro; Feraco, Alessandra; Armani, Andrea; Camajani, Elisabetta; Gorini, Stefania; Strollo, Rocky; Padua, Elvira; Caprio, Massimiliano; Bellia, Alfonso (Frontiers in Nutrition, 2024)
Introduction This study investigates the interplay between body composition, dietary patterns, and physical activity across genders, focusing on gender-specific differences in food preferences and eating behaviors. Understanding these interactions is crucial for developing targeted nutritional and lifestyle interventions. Methods A cross-sectional study was conducted with 1,333 participants (58.7% female, 41.3% male), aged 18–65 years. Participants were categorized into tertiles based on their fat mass to fat-free mass (FM-to-FFM) ratio. Data on dietary choices, eating behaviors, and physical activity were collected and analyzed to identify gender-specific trends. Results Significant gender-specific differences were observed in food preferences and eating behaviors. Males experienced greater hunger in the late afternoon, while females felt more hunger in the morning. Males showed a preference for processed and red meats, whereas females preferred cooked vegetables. Eating behaviors such as meal skipping, uncontrolled eating, nocturnal eating, and taste preferences (sweet or salty) varied distinctly between FM-to-FFM tertiles and genders. Higher FM-to-FFM ratios correlated with lower physical activity levels, particularly in strength training and general sports engagement. Discussion These findings highlight the complex interactions between body composition, dietary habits, and lifestyle factors, emphasizing gender-specific differences. The results suggest that body composition and BMI significantly impact health-related behaviors, necessitating tailored interventions to address these differences and promote healthier lifestyles.